2015
DOI: 10.1371/journal.pone.0125434
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cyprinid Herpesvirus-3 (CyHV-3) Encoded MicroRNAs

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs involved in post-transcriptional gene regulation. Some viruses encode their own miRNAs and these are increasingly being recognized as important modulators of viral and host gene expression. Cyprinid herpesvirus 3 (CyHV-3) is a highly pathogenic agent that causes acute mass mortalities in carp (Cyprinus carpio carpio) and koi (Cyprinus carpio koi) worldwide. Here, bioinformatic analyses of the CyHV-3 genome suggested the presence of non-conserved precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 127 publications
0
28
0
Order By: Relevance
“…Dysregulation of miRNAs in diseases especially in tumor has attracted extensive attentions in recent years (7)(8)(9)(10)(11)(12). Mounting evidences have demonstrated that aberrant expression of several miRNAs is associated with survival outcome of cancer patients (27,28) and therefore could be regarded as potential therapeutic targets for these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of miRNAs in diseases especially in tumor has attracted extensive attentions in recent years (7)(8)(9)(10)(11)(12). Mounting evidences have demonstrated that aberrant expression of several miRNAs is associated with survival outcome of cancer patients (27,28) and therefore could be regarded as potential therapeutic targets for these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences have revealed that altered expression of miRNAs play an important role in tumorigenesis of many human cancers (7)(8)(9). In the mean time, studies have demonstrated that a single cancer can be driven by different miRNAs (7,10,11), while a single miRNA can be found aberrant expressed in different cancers (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary bioinformatics analysis of the viral genome suggested the presence of pre-miRNA, and deep sequencing of the microtranscriptome confirmed the existence of some of the predicted miRNAs [131]. Two pre-miRNAs were found in cells infected in vitro and the corresponding miRNAs were detected in infected animals.…”
Section: Applications Of Ngs To Fish Virology: Some Successful Examplesmentioning
confidence: 99%
“…The vast majority of viral miRNAs identified so far were reported to be expressed by members of the Herpesviridae family (8,14,16,26) and at least one member of the Alloherpesviridae family (27). Viral miRNAs were characterized as the most recently discovered weapons in herpesvirus genomes.…”
Section: Herpesviruses and Mirnasmentioning
confidence: 99%